2015
DOI: 10.1080/01419870.2015.1023822
|View full text |Cite
|
Sign up to set email alerts
|

To whom do national days matter? A comparison of national belonging across generations and ethnic groups in the Netherlands

Abstract: This paper studies to what extent participating in days for national commemoration and celebration is associated with feelings of national belonging, and to what extent this is comparable across generations and ethnic groups. Utilizing data from a national survey (N = 4,505), three major national days in the Netherlands are examined. We find that whereas participation in Queen's Day is associated with national belonging for all generations, for Remembrance Day this holds only for the generation born between 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
(52 reference statements)
0
17
1
Order By: Relevance
“…(1 = not at all -5 = very important). b Coopmans, Lubbers, and Meuleman (2015) found that for citizens with a non-Western origin, participating in national days is associated with national belonging more strongly than for citizens with a native Dutch background. That might explain the non-significant relation between being an immigrant and feelings of national belonging in this study.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…(1 = not at all -5 = very important). b Coopmans, Lubbers, and Meuleman (2015) found that for citizens with a non-Western origin, participating in national days is associated with national belonging more strongly than for citizens with a native Dutch background. That might explain the non-significant relation between being an immigrant and feelings of national belonging in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Many stimulating studies have empirically demonstrated the positive relationship between participation in national ceremonies and feelings of national belonging (Coopmans, Lubbers, and Meuleman 2015;Fozdar, Spittles, and Hartley 2015;Lubbers and Meuleman 2016;Meuleman and Lubbers 2013). These studies are based on cross-sectional data (feelings of national belonging and participation in national commemorations are measured at the same point in time) and, as a result, they do not provide information on the direction of the relationship between participation in national commemorations and feelings of national belonging.…”
Section: Previous Empirical Studiesmentioning
confidence: 99%
See 3 more Smart Citations